Morphometric Analysis of Body and Internal Organs of Male Dusky Pademelon (Thylogale brunii) from Traditional Hunting in Merauke Regency - Maria Magdalena Nay Nadu Lesik; Irine Ike Praptiwi; Desmina Kristiani Hutabarat (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The dusky pademelon (Thylogale brunii) is an endemic marsupial of southern Papua for which morphometric information related to developmental maturity remains limited. This study aimed to evaluate differences in external body measurements and internal organ morphometry of male dusky pademelons across maturity stages (subadult and adult) and to identify practical morphological indicators relevant to conservation and sustainable use.. Methodology: Four male individuals (two subadults and two adults) obtained through traditional hunting in Kampung Wasur, Merauke Regency, were examined. External measurements included body weight, body length, head length, tail length, ear length, limb lengths, and chest circumference. Internal observations comprised pelage colour, dentition characteristics, and the weights of the liver, kidneys, and testes. Differences between maturity stages were assessed using nonparametric statistical analyses. Findings: Chest circumference was the only external parameter showing a significant difference between subadult and adult males (p = 0.0237), indicating greater thoracic development in mature individuals. Other external measurements were not statistically different, although adults consistently showed larger body dimensions. In contrast, internal organ morphometry revealed marked increases in liver, kidney, and testicular weights in adults, reflecting advanced metabolic and reproductive maturity. Age-related changes in dentition and fur coloration further supported maturity differentiation. Given the limited sample size, these findings should be interpreted cautiously. Contributions: This study provides the first integrated morphometric baseline for male T. brunii in southern Papua. Chest circumference and internal organ development emerge as informative indicators of maturity, offering practical value for field-based age classification and community based wildlife management